Exploring the Role of Organizational Culture in Developing Organizational Citizenship Behavior (OCB) through the Implementation of Learning Organization and Information Technology in SMEs - Susilowati Ningsih; Ari Anggarani Winadi Prasetyoning Tyas (Jurnal Minfo Polgan, 2024)
Organizational Citizenship Behavior (OCB) refers to employees' extra-role behaviors that support the overall functioning of an organization. In the context of Small and Medium Enterprises (SMEs), the combination of a strong organizational culture, the implementation of a learning organization approach, and the utilization of Information Technology (IT) can create synergies that foster the development of OCB. The aim of this research is to explore how organizational culture can foster OCB through the implementation of a learning organization and information technology in SMEs. This study is a literature review employing a qualitative approach. Data were collected from scholarly articles obtained through Google Scholar from 1995 to 2024 using relevant keywords. The findings indicate that in the context of globalization and rapid technological advancement, the role of organizational culture, the implementation of learning organization concepts, and the use of information technology are key factors in developing OCB in MSMEs. OCB, encompassing voluntary behaviors beyond official duties, has a significant positive impact on productivity and overall organizational performance. A strong organizational culture, the principles of a learning organization, and prudent information technology usage can synergistically work to enhance OCB in SMEs.